Fast Fashion, Fashion Brands and Sustainable Consumption - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the connection between fast fashion brands and customer-centric sustainability. It highlights what consumers can do with fast fashion and the important aspects that need to be addressed to make fast fashion sustainable. Fast fashion is an inevitable element in today's fashion business cycle and its adverse impacts on sustainable fashion are a major issue.
Fast fashion & Sustainable consumption -- Luxury and fashion brand communication differentiation for sustainable consumer -behavior -- Fashion Brands and Consumers approach towards Sustainable Fashion -- Motives of Sharing: Examining Participation in Fashion Reselling & Swapping Markets.
Keywords: Manufactures; Sustainability; Business logistics; Industrial engineering; Production engineering; Consumer behavior; Machines, Tools, Processes; Sustainability; Supply Chain Management; Industrial and Production Engineering; Consumer Behavior